Waste Treatment in the Food Processing Industry - Wang, Lawrence (CRC Press, 2009)
Many standard industrial waste treatment texts sufficiently address a few major technologies for conventional in-plant environmental control strategies in the food industry. But none explore the complete range of technologies with a focus on new developments in innovative and alternative technology, design criteria, effluent standards, managerial decision methodology, and regional and global environmental conservation specific to the food industry. Until now. Waste Treatment in the Food Processing Industry provides in-depth coverage of environmental pollution sources, waste characteristics, control technologies, management strategies, facility innovations, process alternatives, costs, case histories, effluent standards, and future trends. It delineates methodologies, technologies, and the regional and global effects of important pollution control practices.